Доля людини в одній архівній справі як дзеркало політики колективізації в українському селі - Студьонова, Л. (Сiверянський лiтопис, 2019)
У статті розповідається про згуртування селян Борзнянського району Чернігівської області для протидії колективізації та знищення так званих куркулів, до яких,
за висновком місцевої влади, належав малописьменний селянин Гаврило Терентійович
Савченко (1888 – 23.01.1931) – уродженець села Головеньки, член Головеньківської
контрреволюційної організації «Повстанком України». До 2018 року достовірна
інформація про його долю після арешту не була відома. Звернення до ГДА СБУ дало
позитивний результат. Надано електронну копію справи Г. Т. Савченка, розсекречення
якої відбулося у 2011 році. Автором проаналізовано матеріали цієї справи і зроблено
відповідне резюме. Розкрита таємниця загибелі ще однієї людини з мільйонів жертв
сталінської політики колективізації в українському селі. The article deals with the unification of the peasants of the Borznyansky district of the
Chernihiv region to counteract the collectivization and destruction of the so-called kulaks
(the richest peasants), to which, according to local authorities, belonged to a poorly written
peasant Gavrylo Terentievich Savchenko (1888, Jan. 23, 1931) – a native of the village of
Holovenky of Borznyansky district. This became possible after receipt of the electronic copy of
the case of G.T.Savchenko from the Branch State Archive of the Security Service of Ukraine,
declassified only in 2011. It consists of 13 documents in 20 sheets, which give a precise picture
of what happened to a hard-working, wealthy peasant, caring father of a large family who
was shot in 1931. However, his family in 1956 was informed that G. T. Savchenko in 1935
died of atherosclerosis.
The author analyzes all documents of this case: a certificate signed by the chairman of the
Golovenkiv Village Council of December 28, 1930; Report of the Chekist informer «Lonely»;
protocols of interrogations by G. T. Savchenko and those involved in the case; minutes of
spectacle rates; indictment; a document about rehabilitation of G. T. Savchenko.
The content of Articles 54-4, 54-11, 54-2 of the Criminal Code of the Ukrainian SSR,
which became a shooting sentence for G. T. Savchenko, is disclosed. They were unlawful.
This is evidenced by the document «Conclusion on SA T. Savchenko on the materials of
the criminal case (Arch. No. 5,1834, t.509») of June 29, 1989, signed by V. I. Lisnyi, Senior
Advisor of the Prosecutor’s Office of the Prosecutor’s Office of the Ukrainian SSR, and
deputy head of the KGB investigating department USSR, Lieutenant Colonel V.I. Pristaykom.
Thus, the article reveals the mystery of the death of one more person from the millions of
victims of Stalin’s policy of collectivization in the Ukrainian village.